Thermal performance evaluation of phase changing materials in double glazing units for office buildings in Egypt - Omar Abdel-Rahman; El Rouby; Mohamed Moemen Afify (Scientific Reports)
Abstract Nowadays glass curtain walls are used widely in modern buildings as they offer a significant aesthetic appearance and provide the building with natural lighting. However, their poor thermal resistance leads to excessive usage of mechanical systems to achieve thermal comfort which in turn increases the energy consumption in buildings. The proper integration of the unique properties of the PCM could effectively enhance the thermal performance of buildings therefore, the main objective of this research is to examine and validate the effect of using phase change material (PCM) on the building thermal performance especially when integrated with double glazing unit (DGU). The research examined comprehensively the effect of using PCM with DGU by undergoing a field experiment and comparing the results with a simulation model using Design Builder (DB) -energy plus simulation tool. After validating the simulation model, DB was used to examine the effect of using PCM double glazing unit with a multi-story office building in three different climatic regions in Egypt covering humid, mild, and hot arid regions. The results showed that using petroleum jelly as a PCM with DGUs will lead to a significant effect in reducing the usage of mechanical systems in cooling the building spaces by 8.91%, 8.62%, and 8.07% in Cairo, Alexandria, and Aswan consecutively from the total yearly cooling electric consumption.